2022
DOI: 10.2298/tsci210309185b
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of using phase change material for solar pond insulation

Abstract: Solar ponds are systems that store solar energy in salt water as heat energy. In order to store heat energy for a long time in solar pond, the heat insulation should be done well. In this study, the effect of phase change materials (PCMs) was investigated to improve the insulation of the pond and to store the heat energy for a longer time. The melting temperature is a key parameter in the selection of PCMs. The temperature distribution of the solar pond was examined and PCMs with melting temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…It was demonstrated that air temperature, radiation, and humidity have a significant relation with the evaporation rate. Bozkurt 9 investigated the effect of different PCMs placed on the walls of the solar pond on the heat storage performance of the system. The increase in the heat storage rate of the pond using PCM was calculated numerically and compared with the pond without PCM.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that air temperature, radiation, and humidity have a significant relation with the evaporation rate. Bozkurt 9 investigated the effect of different PCMs placed on the walls of the solar pond on the heat storage performance of the system. The increase in the heat storage rate of the pond using PCM was calculated numerically and compared with the pond without PCM.…”
Section: Introductionmentioning
confidence: 99%
“…Bozkurt investigated the effect of PCMs on improving the insulation of the pond. He determined that using the PCM allowed heat energy to be stored in the SGSP for a longer time [10]. Ihsan et al investigated the impact of a PCM on the efficiency and applicability of a SGSP, ultimately showing that the use of PCM allows to stabilize the LCZ temperature by the latent heat, thus enhancing the SGSP's efficiency during the colder seasons [11].…”
mentioning
confidence: 99%